Financial Liberalization and Money Demand in Asean Countries : Implications for Monetary Policy - Dekle, Robert (IMF Working Papers; Working Paper ;, 1997)
This paper examines the impact of financial market development and liberalization on money demand behavior in Indonesia, Malaysia, Singapore, and Thailand since the early 1980s. The empirical results indicate continuing instability in the interaction of money growth, economic activity, and inflation. Rapid growth and ongoing changes in financial markets suggest that policy needs to be guided by a wider set of monetary and real sector indicators of inflationary pressures. The feasibility of alternative policy frameworks--including nominal exchange rate targets, and inflation targets--is discussed in the context of the substantial and sustained increase in foreign capital inflows.